GESTATIONAL TROPHOBLASTIC DISEASE: EXPERIENCE AT NAWABSHAH HOSPITAL - Nizam, Khairunnisa; Haider, Gulfareen; Memon, Nizamuddin; Haider, Ambreen (Journal of Ayub Medical College Abbottabad, 2009)
Background: Gestational Trophoblastic Disease (GTD) is a heterogeneous group of diseases that includes partial and complete hydatidiform mole, invasive mole, choriocarcinoma and placental site trophoblastic tumour. The incidence of GTD varies in different parts of the world. The malignant potential of this disease is higher in South East Asia in comparison to western countries. Objectives of study were to determine the frequency, clinical presentation and management outcomes of GTD. This retrospective, descriptive case series was conducted in the Department of Obstetric and Gynaecology Nawabshah Medical College Hospital, from 1st Jan 2007 to 30th Dec 2007. Methods: The case records of all the gestational trophoblastic cases during study period were analysed regarding their history, clinical examination, investigations, treatment and follow-up. The main outcomes were measured in terms of duration, antecedent pregnancy, investigations, treatment and the follow-up. Results: There were a total of 1056 Obstetric admissions during the study period, which included 30 cases of trophoblastic disease with a frequency of GTD was 28 per 1000 live births. Of these 30 cases, 21 (70%) patients had hydatidiform mole, 7 (23.3%) patients had invasive disease and 2 (6.6%) patients had choriocarcinoma. Twenty three patients (76.6%) received chemotherapy while 25 (83.3%) patients had suction evacuation and 4 (13.3%) patients underwent hysterectomy. Among all patients, 29(96.7%) fully recovered and 1 (3.3%) died because of extensive disease; metastasis extending up to brain. Conclusion: Frequency of GTD was higher compared to national and international studies. The disease was common in extremes of ages, low para and grand multiparous women. Hydatidiform mole was the commonest type of trophoblastic disease in these patients. Most common presenting complaint was bleeding per vagina followed by pain in lower abdomen. Keywords: Gestational trophoblastic disease, Hydatidiform mole, Management.